PENYEBAB KONFLIK KARYAWAN PERUSAHAAN X DI KELURAHAN KAMPUNG PONDOK KOTA PARIAMAN - Musfi, Wahyuni Tiara; kasih, Fitria; Alfaiz, Alfaiz (Bimbingan dan Konseling, 2014)
This researched was based of Â phenomenan which the researher looks in the field, such as conflict that are appeared every employee, employee often works happening conflict, least interaction, least seriously. Focus in research alike: 1) The problems are relationshiply of work that are experienced by employee. 2) The problems of different perception which are appeared for employee. 3) The problem of different purpose for employee.Kinds of this researh is qualitative research that are study case characteristic about giving complete effort, detail information, and intensif expressing the background of cause confilict that are experinced by employee at enterprise x. The technique of data analysis which is used narative analysis. Key informant in this research sums 2 person. 1 man that worked since 2 year, and 1 man which have worked since 2 year. Thus, adding informant 3 person include 1 leadership and 2 partner in working.The result of this research get points that 1) The problems are relationship working least feel by employee, because they want to only work lightly. Together working, need helping, and least interaction become conflict in working. 2) The problems of different perception are often experienced by employee, because they think good friend if leadership comes at office, and also among them corupted, because there is not clear money. 3) The problem of differen purpose in working, because employee have personality goal that want to get more lightly work that other employee, there are together work in order to advance technology. This research is hoped getting advantages for: 1) Employee. They can recognize the cause of conflict in working. 2) Writer. To add insight and knowledge about causing of conflict employee. 3) Leadership. To more wise and understand the condition of employee at office. 4) For office worker. They can prepare college students to get suggetions from the lecturer. 5) For the next researcher. In order to know the cause of conflict in work world and can continue about the step of finishing the conflict of employee in work world.Â Â